1996
DOI: 10.1183/09031936.96.09112207
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-phenotype relationships in a cohort of adult cystic fibrosis patients

Abstract: G Ge en no ot ty yp pe e--p ph he en no ot ty yp pe e r re el la at ti io on ns sh hi ip ps s i in n a a c co oh ho or rt t One hundred and ten adult CF patients were classified according to the expected effect of their mutations on cystic fibrosis transmembrane conductance regulator (CFTR) protein: Group 1 (n=48) included ∆F508 homozygotes; Group 2 (n=26), patients with two " "severe" " mutations and no expected CFTR production; Group 3 (n=17), patients with expected partly functional CFTR corresponding to at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 27 publications
0
8
0
6
Order By: Relevance
“…The tests were performed in the Institute for Mother and Child in Warsaw. The sample was divided into four groups according to the genotype effect on the chloride canal function [18]. The patients with homozygote DF508, where production of protein CFTR was deficient, were counted among group 1.…”
Section: Methodsmentioning
confidence: 99%
“…The tests were performed in the Institute for Mother and Child in Warsaw. The sample was divided into four groups according to the genotype effect on the chloride canal function [18]. The patients with homozygote DF508, where production of protein CFTR was deficient, were counted among group 1.…”
Section: Methodsmentioning
confidence: 99%
“…Modifier genes may play a significant role in determining the severity of CF. Furthermore, for a single mutation such as F508del, the pulmonary status may range from insignificant to severe [19, 20]. It is therefore obvious that, whereas classic genotype-phenotype studies in CF are important, they are not sufficient and have to be complemented by the search for environmental effects on the phenotype of patients, to increase the basic knowledge of the disease and to develop new therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Studies focusing on the pulmonary status as a function of the ΔF508 allele dosage reported a whole range of effects from detectable impact of CFTR genotype [37, 39]to none or statistically insignificant [38, 40, 41, 44, 51]. Of the studies using more refined assessment of CFTR mutations, such as those classifying their molecular mechanisms, or extent of the CFTR chloride channel function, some have shown statistically significant correlations between CFTR genotypes and pulmonary status [42, 49, 50]while others have failed to detect a significant association [43, 47]. Some of these discrepancies can be ascribed to differences in experimental design, the size and demographics of the study populations, selection of clinical parameters, the prevalence of ΔF508 and the spectrum of other CFTR mutations in the study populations, methods of statistical evaluation and a variety of factors associated with treatment modalities adopted in a given center.…”
Section: How Do Cftr Mutations Contribute To Clinical Variation In Cf?mentioning
confidence: 99%
“…Initially, cross-sectional studies focused on the impact of the most common mutation ΔF508. Later, with improvement in mutation screening techniques, studies were extended to evaluate the effects of other mutations [37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50]. Studies focusing on the pulmonary status as a function of the ΔF508 allele dosage reported a whole range of effects from detectable impact of CFTR genotype [37, 39]to none or statistically insignificant [38, 40, 41, 44, 51].…”
Section: How Do Cftr Mutations Contribute To Clinical Variation In Cf?mentioning
confidence: 99%